Digestibility and Blood Metabolite Profiles of Chicken Fed Fermented Jatropha Seed Meal - Widiyastuti, T; Prayitno, CH; Iriyanti, N (ANIMAL PRODUCTION, 2013)
This research had been conducted to obtain a feed formula that is capable of supporting optimal production performance  both in broilers and laying hens fed on feed containing fermented jatropha seed meal and addition saccarides. Fifty four broiler and fifty four layer were used.  Nested classification was the experimental design with bird kinds as group, levels of fermented Jatropha curcas meal (JCM-F) (9%, 12%, 15%) as  sub group and  levels of fructooligosaccharida/FOS (0.5%; 1%; 1.5%) as a sub sub group.  There were 3  replications in each treatment. Jatropha curcas meal was fermented with lactid acid bacteria (L. acidophilus and Bifidobacter spp) for 12 x 24 hour in 37oC.  The objective of the research was to evaluate growth, feed consumption, nutrient digestibility (crude protein and gross energy), blood metabolites  (glucose, cholesterol and trgliseride).  The results showed that the type of chicken had significant effect on growth and protein retention. The level of Jatropha curcas meal had significant effect on blood  serum triglyseride concentration.  On the other hand, the level of FOS had no significant effect on all variables. It could be concluded that Jatropha curcas meal  is better as broiler feed than layer feed with 0.5% FOS. However, to be used as feed of laying hens, it requires further optimalization of the fermentation process. Animal Production 15(2):98-105, May 2013